To the Analyzing Instrument and Beyond: Reconstructing Evenly Hovering Attention - Gupta, Rajan (Auckland University of Technology, 2008)
This dissertation explores the attentional processes by which the psychotherapist arrives at clinical inferences in his work with clients. In particular, the focus is on one of the early tenets of psychoanalytic technique, Freud’s direction around evenly hovering (suspended)/free-floating attention as a vehicle for the registration of the unconscious material embedded in the client’s communication/free association. A systematic review of the literature was conducted, drawing on the existing knowledge base for narratives around experiences of ‘unconscious knowing’ by psychotherapists connected to the idea of evenly hovering attention. This consisted of the work of four psychoanalytic clinicians: Reik, Isakower, Jacobs and McLaughlin – who have built on Freud's concept, and have to that extent offered their own interpretation/s of how evenly hovering attention comes to occupy the central role within psychoanalytic practice. The intent was to bridge, make sense of, and interpret these different representational systems/structures in order to arrive at some implications to inform psychotherapy practice. The discussion underscores how the psychotherapist’s use of non-linear, undirected and associative mental processes, both within and outside the therapy situation, furthers the understanding of unconscious processes. Vignette/s from my own clinical practice and those of the four psychoanalytic clinicians reviewed, are included to typify the operation of these respective forms of evenly hovering attention.
Keywords: Evenly suspended attention; Third ear; Pscyhoanalysis; Analyzing instrument; Jacobs use of the self; Mclaughlin transference sanctuaries